Educational Learning in Implementing Character Education - Andini, Nanda Dwi (Berpusi Publishing, 2025)
The purpose of this research is to find out how educational learning is in implementing character education. In relation to educational learning, to form good character is through teaching guidance activities and providing character knowledge to each individual. The results of this study are that the character education learning process is a series of learning activities that take place both in the classroom and outside the classroom which seeks to make students not only master the material but also make students know, realize/care about and internalize values and turn them into behavior. This type of research uses a qualitative descriptive approach. Literature study is an effort to explore and collect information or data by reviewing various reference books, journals that are relevant to the theme or issue that is the object of the writing discussion. The data collection technique used by journal writers is by searching and reviewing index reference books for journals related to the title of this research. Meanwhile, to find out the results and analyze this journal data by collecting real data by interviewing and observing.